Characterization of the renal phenotype in RMND1‐related mitochondrial disease. Issue 12 (30th September 2019) - Shayota, Brian J.; Le, Nhon T.; Bekheirnia, Nasim; Rosenfeld, Jill A.; Goldstein, Amy C.; Moritz, Michael; Bartholomew, Dennis W.; Pastore, Matthew T.; Xia, Fan; Eng, Christine; Yang, Yaping; Lamb, Dolores J.; et al.
Abstract: Background: The nuclear encoded gene RMND1 (Required for Meiotic Nuclear Division 1 homolog) has recently been linked to RMND1‐related mitochondrial disease (RRMD). This autosomal recessive condition characteristically presents with an infantile‐onset multisystem disease characterized by severe hypotonia, global developmental delay, failure to thrive, sensorineural hearing loss, and lactic acidosis. Renal disease, however, appears to be one of the more prominent features of RRMD, affecting patients at significantly higher numbers compared to other mitochondrial diseases. We report the clinical, histological, and molecular findings of four RRMD patients across three academic institutions with a focus on the renal manifestations. Methods: Four patients were identified for the purpose of this study, all of whom had molecular confirmation at the time of inclusion, which included the common pathogenic variant c.713A>G (p.N238S) as well as the three rare variants: c.485delC (p.P162fs), c.533C>T (p.T178M), and c.1317 + 1G>C splice donor variant. Medical history and laboratory findings were collected from the medical records and medical providers. Results: In this study, all four patients developed renal disease characterized as tubulopathy (3/4), renal tubular acidosis (2/4), interstitial nephritis (1/4), and/or end‐stage renal disease (4/4) necessitating renal transplantation (2/4). Histological evaluation of renal biopsy specimens revealed generalized tubular atrophy and on electron microscopy, abundant mitochondria with pleomorphism and abnormal cristae. Conclusion: Our experience with RRMD demonstrates a specific pattern of renal disease manifestations and clinical course. Patients are unlikely to respond to traditional chronic kidney disease (CKD) treatments, making early diagnosis and consideration of renal transplantation paramount to the management of RRMD. Abstract : RMND1‐related mitochondrial disease (RRMD) is a complex mitochondrial condition that has a particularly high risk of severe and early‐onset renal disease compared to other mitochondrial disorders. In this study of four patients, we have shown that the clinical phenotype may include tubulopathy (3/4), renal tubular acidosis (2/4), interstitial nephritis (1/4), and/or end‐stage renal disease (ESRD) necessitating renal transplantation (4/4). Additionally, patients are unlikely to respond to traditional chronic kidney disease (CKD) treatments, making early diagnosis and consideration of renal transplantation paramount to the management of RRMD.